Analysis of the Financial Performance of the Republic of Indonesia Fajar Sinjai Employee Cooperative - Rasyid, A. Meylani Dwi Putri; Ruliati, Firman Syah, Ruliati (YUME : Journal of Management, 2025)
Introduction/Main Objectives: This research examines the financial performance of the Fajar Sinjai Republic of Indonesia Employees Cooperative (KPRI) during the 2019–2023 period. This topic is interesting because cooperatives have an important role in the economic empowerment of members, and financial performance assessment is a crucial aspect to ensure the sustainability of their operations. Background Problems: The problem in this research is the condition of KPRI Fajar Sinjai's financial performance in terms of liquidity, solvency and profitability ratios based on the standards of Minister of Home Affairs Regulation No. 47 of 2022. Novelty: This research makes a contribution by applying the latest financial evaluation standards from Permendagri No. 47 of 2022 in the context of cooperatives, which is rarely done comprehensively in previous literature. Research Methods: The method used is descriptive quantitative with a financial ratio analysis approach, including Current Ratio (CR), Debt to Equity Ratio (DER), and Return on Assets (ROA), based on KPRI Fajar Sinjai's financial report data for five years. Findings/Results: The research results show that the liquidity ratio (CR) is in the very good category every year, and solvency (DER) shows a significant improvement trend. However, profitability (ROA) fluctuates and tends to decrease at the end of the period. Conclusion: In general, the cooperative's financial condition is relatively healthy in terms of liquidity and solvency. However, a strategy to increase operational efficiency is needed to maintain and increase profitability in the future. This research can be a basis for managerial considerations in making cooperative strategic decisions.Keywords:  Financial Performance, Current Ratio, Debt to Equity Ratio, Return on Assets, Cooperatives